Comparison of digital coincidence modules used at POLATOM and PTB for TDCR and 4πβ(LS)-γ coincidence counters. (October 2020) - Ziemek, T.; Nähle, O.J.; Kossert, K.; Leschitzki, S.; Takács, M.P.; Broda, R.; Listkowska, A.; Tymiński, Z.; Dziel, T.
Abstract: Activity measurements of 3 H, 241 Am and 60 Co solutions were performed to compare digital coincidence modules used at PTB and POLATOM for TDCR and 4πβ(LS)-γ coincidence counting. The activities determined with various coincidence modules connected in parallel to the same counter at PTB were found to be consistent. Observed discrepancies caused by differences in the coincidence resolving time did not exceed 0.14%. Accidental coincidences simulated by a frequency generator were registered, and the coincidence resolving time was determined. Highlights: Comparison of the PTB and POLATOM coincidence modules. Good agreement of 3 H, 241 Am and 60 Co activity measurements. Coincidence resolving time determined using frequency generator.